Dinamika Pemikiran Islam di Indonesia Kontemporer - Puad Hasan; Zaenal Abidin (Edusifa: Jurnal Pendidikan Islam, 2024)
ABSTRACT This article attempts to explore the dynamics of Islamic intellectualism and thought in Indonesia by examining its characteristics, origins, development, actors and struggles. In this context, Islamic thought in Indonesia is understood as a stage in which the understanding and practice of Islam established in the Nusantara is revisited, criticized, deepened and "refreshed". Thus, this study refers to that chapter in the history of Islamic thought in the 20th century, when Muslim scholars in the modern era in Indonesia initiated this thought, developed and experienced ups and downs. In this case, it can be seen that Islamic thought in Indonesia is in fact a response to the former understanding of Islam, which is constantly engaged in "dialogue" with the development of society and has strategic implications for the modern understanding of Islam. Keyword: Islamic thought, Indonesia, Tradition, Modern